Reconstruction of Restorative Justice Mechanisms in Resolving Trading in Influence: A Criminal Law Perspective and Target 16 SDGs - Amrullah, Rinaldy; Putri, Ria Wierma; Putri, Yunita Maya; Riyantika, Annisa (UNISSULA, 2025)
Trading in influence is a form of corruption that has gained increasing attention in Indonesia's legal system. This practice involves leveraging social relationships and access to public officials to gain certain advantages, either directly or indirectly. However, Indonesian law has yet to explicitly criminalize trading in influence as a distinct corruption offense, leading many cases that should fall under this category to be prosecuted under bribery or gratification laws instead. Amid these legal limitations, the concept of restorative justice emerges as an alternative resolution mechanism that focuses more on restitution and reconciliation rather than mere punishment. This study employs a normative juridical approach by analyzing relevant legal regulations and case studies at both national and international levels. From a criminal procedure law perspective, implementing restorative justice in trading in influence cases faces significant challenges, particularly in terms of evidence and victim identification. Nevertheless, this mechanism has the potential to enhance law enforcement effectiveness by promoting transparency, accountability, and the restitution of unlawfully obtained benefits. In the context of implementing Target 16 of the SDGs, the application of restorative justice can strengthen the rule of law and foster more transparent and inclusive institutions. Therefore, clearer regulatory reforms are necessary to accommodate restorative justice as a viable approach to addressing trading in influence as part of Indonesia's broader anti-corruption efforts.